A new method for extracting the state equations from bond graph of dynamical systems (SEBG method). Issue 6 (18th August 2021) - Aftabi Talami, Mohammad; Jamali, Ali; Nariman-zadeh, Nader
Abstract : The bond graph (BG) method is an appropriate tool to model hybrid systems. The automated extraction of state equations from BG is the main drawback of this method. In this paper, a new method has been presented to simply extract the state equations from BG (SEBG method). Initially, SEBG has converted the BG model to the bond-element table (BE-table) to gain all the information of BG in a systematic representation. It has then formed a set of algebraic equations using elements' functions (E-functions) and found the power variables by solving them. Finally, the system's state equations are established using BE table, power variables, state vector, and states' functions, based on the fact that only the relations of inertial and capacity elements contain the first-order differential equations. Moreover, the simplicity and practicality of SEBG have been examined for finding the state equations of two systems.